Economic Benefits and Governance of Guiding Barrier Fishing Gear in White-Spotted Spinefoot Fish Fishing Activities (Siganus canaliculatus, Park 1797) In Bontang City Waters - Kamilan, Kamilan; Ramang, Muhammad Syahrir; Susilo, Heru; Fitriyana, Fitriyana; Nurfadilah, Nurfadilah; Auliansyah, Auliansyah (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
Guiding barrier fishing gear has been used in recent years in the mangrove, seagrass, and coral ecosystem areas of Bontang City. In previous studies, the main target, white-spotted spinefoot fish, has depreciated and degraded as a result of overfishing. This study calculates the economic benefits and attempts to analyze the management policy of guiding barrier fishing gear to overcome the depreciation and degradation problems. To calculate the economic benefits, the fisheries production approach was used, while the policy analysis used the interpretive structural model technique. During the peak season of white-spotted spinefoot fish, the average fisherman earns up to IDR400,750 per day, with a minimum of IDR103,000 and a maximum of IDR1,904,000. The optimal fishing period is nine months, after which fishermen will stop fishing in Ramadan, August, and September. There are six guiding barrier fishing gear management policies, namely: 1) open and close systems at the installation site; 2) increase the mesh size used; 3) reduce the number; 4) moratorium on new installations; 5) limit the number of owners for each fisherman; and 6) regulate the distance between guiding barrier fishing gear. Of the six policy alternatives, the top priority is to increase the mesh size used.